2019
DOI: 10.3390/ijerph16203919
|View full text |Cite
|
Sign up to set email alerts
|

Social and Psychological Predictors of Body Mass Index among South Africans 15 Years and Older: SANHANES-1

Abstract: This study investigated how psychological distress and the proxies for social position combine to influence the risk of both underweight and overweight in South Africans aged 15 years and older. This was a cross-sectional study that included 2254 men and 4170 women participating in the first South African National Health and Nutrition Examination Survey (SANHANES-1). An analysis exploring the associations of social and mental health characteristics with body mass index (BMI) was conducted using binary and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Furthermore, the rise in overweight/obesity rates is attributable to socio-demographic [11], environmental [12], behavioral [12] and genetic factors [13]. Women have been reported to have a higher risk of overweight/obesity compared to men, while being employed and having a higher level of education were associated with increased risks for overweight and obesity [14]. Higher educational attainment in women and higher socioeconomic status (SES) in men were associated with higher BMI [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the rise in overweight/obesity rates is attributable to socio-demographic [11], environmental [12], behavioral [12] and genetic factors [13]. Women have been reported to have a higher risk of overweight/obesity compared to men, while being employed and having a higher level of education were associated with increased risks for overweight and obesity [14]. Higher educational attainment in women and higher socioeconomic status (SES) in men were associated with higher BMI [15].…”
Section: Introductionmentioning
confidence: 99%
“…While the prevalence of underweight in men is 4 times that of women, the prevalence of obesity in women is almost 4 times that of men [2]. Body image seems to be one of the important factors that can explain the stable underweight prevalence in men and the escalating prevalence of obesity especially in women and those individuals who fall below the poverty index line (PIL) in South Africa [1][2][3][4]. In fact, Shisana et al [1] and Mchiza et al [5] have shown that the majority of South Africans who present with negative body image (BI) tend to also present with unhealthy body size (underweight and obesity).…”
Section: Introductionmentioning
confidence: 99%
“…Underweight and obesity co-exist in the same households in South Africa [1,2]. While the prevalence of underweight in men is 4 times that of women, the prevalence of obesity in women is almost 4 times that of men [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations